Promoting Insight in Scientific Innovation: The Effects of Function-Construction Maps. Issue 1 (2nd January 2019) - Zhao, Yanmei; Zhang, Zhengtang; Xu, Wenjian; Zhang, Qinglin
Abstract : Although research from a range of fields indicates the importance of innovation for progress in those fields, there is not yet a set of best practices for promoting insights that lead to scientific innovation. This article proposes and tests the hypothesis that function-construction maps based on prototype and heuristic theory lead to increased insight in college students. The study selected scientific innovation materials from an experimental materials database, extracted the underlying prototype solutions, and added redundant information as a condition for testing student insight and problem-solving ability. Results indicated that redundant innovation material tested reasoning ability more effectively than did nonredundant material, that this effect only appeared in the absence of function-construction maps, and that student insight was enhanced only when students were taught to extract function-construction maps from the material and were allowed to get their bearings by accessing the test questions before the prototypes.